Housing Stratification in the European Union - MuftakhovaAlmira; Kozyreva, Larisa (Journal of Economic Sociology, 2018)
The article presents the results of a comparative analysis of the housing systems of market countries in Western Europe and countries with transit economies in Eastern Europe. The analysis focuses on the housing problems of stratification which is understood as social inequalities while satisfying housing needs. The empirical base was provided by the descriptive statistics of socio-demographic and intercountry differences presented by Eurostat and NGO Housing Europe on the basis of which the indicators of housing stratification. The study showed a discrepancy between living conditions in the East of Europe to the European average and a significant difference from Western countries in accessing the needs of natural housing. An analysis of the differences in the distribution of the population by place of habitation and types of citizens residence made it possible to draw a conclusion about a kind of “cargo cult” formed in the former socialist countries with respect to residential real estate. As a result of the ranking of data on the criterion of maturity and effectiveness of housing policies of different countries and analysis of the practice of their realization the term “rumanianization” characterizing the worst way of organizing relations in the housing sphere was proposed. In this case the main way to meet housing needs is simple private ownership of housing (unserved and unencumbered); as the only place of dwelling (residence) is a dwelling, which is in private ownership, and from this the real estate market has a speculative character; there is little or little development of the institution of mortgage, housing loans; rent and hiring (any kinds) are not taken into account by statistics and are outside the state control zone, etc. The practical significance of the study lies in the fact that the inclusion of the positive European experience in reducing the degree of social inequality in the housing sector will not only improve the efficiency of the development and implementation of national and regional housing programs but also in the future provide transition to a socially oriented type of economic development.